Human rights : politics and practice - Goodhart, Michael E., 1969- (2013)
This book provides a comprehensive introduction to human rights that takes students beyond a purely legal perspective to look at theoretical issues and practical approaches. It brings together international experts including political scientists, philosophers, lawyers, and policy-makers, and is up to date with a constantly evolving field. The second edition sees an expansion of theoretical content, and introduces students to areas of growing importance, including non-western approaches to human rights. It also looks at feminist approaches, and includes more material on group and individual rights. In addition, the book includes more critical perspectives, and there is more material on global civil society and children's human rights. A new concluding chapter charts the possible future development of human rights and ensures that students are up to date.
Includes bibliographical references (p. [441]-477) and index.
Keywords: Human rights -- Textbooks; Human rights; 2; Textbooks